2017
DOI: 10.4103/0973-1075.197944
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of phantom limb pain, stump pain, and phantom limb sensation among the amputated cancer patients in India: A prospective, observational study

Abstract: Introduction:The phantom limb pain (PLP) and phantom limb sensation (PLS) are very common among amputated cancer patients, and they lead to considerable morbidity. In spite of this, there is a lack of epidemiological data of this phenomenon among the Asian population. This study was done to provide the data from Indian population.Methods:The prevalence of PLP, stump pain (SP), and PLS was prospectively analyzed from the amputated cancer patients over a period of 2 years in Dr. B.R.A. Institute Rotary Cancer Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 49 publications
0
44
1
2
Order By: Relevance
“…Sex, age and traumatic cause of amputation were the most commonly assessed of these proposed risk factors. Sex was consistently not associated with PLP in six studies representing a total of 1836 participants [3,5,13,38,51,52]. Age was not associated with PLP in three studies representing a total of 1062 adult participants [5,38,52] but higher age was positively associated with PLP (weak association) in one study representing a total of 716 adult participants [53].…”
Section: Plos Onementioning
confidence: 86%
See 2 more Smart Citations
“…Sex, age and traumatic cause of amputation were the most commonly assessed of these proposed risk factors. Sex was consistently not associated with PLP in six studies representing a total of 1836 participants [3,5,13,38,51,52]. Age was not associated with PLP in three studies representing a total of 1062 adult participants [5,38,52] but higher age was positively associated with PLP (weak association) in one study representing a total of 716 adult participants [53].…”
Section: Plos Onementioning
confidence: 86%
“…The meta-analysis that stratified the studies by country developmental status suggested that the prevalence of PLP was significantly lower in developing countries compared to developed countries [53.98% vs 66.55%; p = 0.03]. This discrepancy is surprising and might be an artefact of selection bias linked either to the lower recruitment success rates (57.9% -68.4%) seen in most of the included studies conducted in developing countries [3,34]. The strategy of recruiting participants from amongst patients receiving follow-up medical care may have contributed to underestimation of PLP prevalence if amputees with PLP without continuing medical care were excluded from samples (in developing countries), or overestimation if having PLP made amputees more likely to remain in medical care (in developed countries).…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation
“…Multiple studies have evaluated the prevalence of symptomatic phantom limb pain and residual limb pain in amputees to denote the magnitude of these morbidities. Reported rates of symptomatic phantom limb pain and residual neuroma pain among amputee patients are 9% to 67% and 2% to 25%, respectively 2 - 4 , 6 , 14 , 15 . In a military population, Carlen et al found that 67% of soldiers with traumatic amputation had phantom limb pain in the first few months after surgery 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Initially used for patients with shoulder disarticulation or who have had a transhumeral amputation, TMR transfers the transected peripheral nerves that no longer have motor or sensory end-organs into recipient motor nerves of residual muscle in the amputated extremity 2 - 4 , 6 , 14 . While initially developed in an effort to “bioamplify” myoelectric signals for advanced bioprosthetic limbs, early clinical results demonstrated an improvement in neuroma-related pain and other postoperative pain symptoms 15 - 21 .…”
mentioning
confidence: 99%